Utilizing vaccination for Porcine Circovirus Type 2 as a tool to aid elimination of PCV2 from swine populations - Potter, M. L.; Nietfeld, Jerome C.; Oberst, Richard D.; Henry, Steven C.; Tokach, Lisa M.; Hays, Michael P.; Fuller, A.; Straw, B. E.; Bates, R. O.; Hesse, Richard A.; Rowland, Raymond R. R.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2012)
A total of 928 pigs from the Swine Teaching and Research Centers at Michigan State University (MSU) and Kansas State University (KSU) and a Kansas commercial farm were used during a 3-year study to determine whether circovirus vaccination influenced porcine circovirus type 2 (PCV2) circulation within a herd and could be used as a tool to eliminate PCV2 from PCV2-positive swine herds. Infection with PCV2 was confirmed in both university herds before circovirus vaccine introduction. After vaccination implementation, vaccinated barrows from consecutive groups were serially tested for viremia. Follow-up antibody and growth testing with vaccinated and nonvaccinated pigs was performed at the KSU farm. In a circovirus-vaccinated commercial herd, testing of non-circovirus-vaccinated pigs for viremia was completed. Environmental swab samples were collected from facilities at the KSU and commercial farms for PCV2 DNA detection. Sera from 0 of 9 MSU vaccinated-cohorts and 3 of 10 KSU vaccinated-cohorts had detectable PCV2 DNA. From follow-up testing, a PCV2 antibody rise after vaccination was detected for vaccinated pigs with no detectable antibody rise for non-vaccinated pigs. Overall growth rate of non-vaccinated pigs tended (P = 0.07) to increase compared with vaccinated pigs. Non-vaccinated pigs became PCV2 viremic at the commercial farm. Viral DNA was detected in the environment of the commercial farm but not in the KSU facilities.Therefore, circovirus vaccine can affect viral circulation on farms but would need to be used in conjunction with other management practices to eliminate PCV2 from most swine populations.
Keywords: Swine; Circovirus; Disease elimination; PCV2; Vaccine